Determinants for craniofacial pains in children 6–8 years of age: the PANIC study. (18th August 2017) - Vierola, Anu; Suominen, Anna Liisa; Eloranta, Aino-Maija; Lintu, Niina; Ikävalko, Tiina; Närhi, Matti; Lakka, Timo A.
Abstract: Objective: Determinants for orofacial pain, headache, morning headache and painful signs of temporomandibular disorders (TMD) were investigated in prepubertal children. Material and methods: The participants were a population sample of 439 children aged 6–8 years. Craniofacial pains, eating meals and snacks, sleep bruxism, sleep quality, sleep-disordered breathing (SDB), psychological well-being, parental education and household income were assessed by questionnaires filled out by the parents. Sleep duration was assessed using a combined heart rate and movement sensor and clinical signs of TMD and dental occlusion by a dentist. The determinants of pain conditions were analyzed using logistic regression. Results: Of all 439 children, 26% had experienced orofacial pain and 31% headache during the past 3 months, 17% had suffered morning headache weekly and 13% had painful signs of TMD in a clinical examination. Restless sleep was associated with increased risk of orofacial pain, the painful signs of TMD and restless sleep with increased risk of headache and restless sleep, sleep bruxism and skipping meals with increased risk of morning headache after adjustment for other independent determinants of these pain conditions. Headache was associated with increased risk for painful signs of TMD. Conclusions: Craniofacial pains are common among prepubertal children. Prepubertal children with sleep bruxism, restless sleep and skipping meals have increased likelihood of craniofacial pains.